Beneficial effects of chrysin on the reproductive system of adult male rats - Ciftci, O.; Ozdemir, I.; Aydin, M.; Beytur, A. (Wiley, 2012)
In this study, the beneficial effect of chrysin, a natural flavonoid currently under investigation due to its important biological activities, on reproductive system of rats was investigated. Rats (n = 16) were divided randomly into two equal groups. Rats in control group were given corn oil as carrier. Chrysin was orally administered at the dose of 50 mg kg-1 per day by gavages, and it was dissolved in corn oil for 60 days. Tissue thiobarbituric acid reactive substances (TBARS) and glutathione (GSH) levels, antioxidant enzyme activity (CAT, SOD and GSH-Px), sperm parameters (motility, concentration and abnormal sperm rate), reproductive organ weight (testes, epididymis, vesicula seminalis, prostate) and serum testosterone levels were determined in the rats. Our results indicated that chrysin significantly increased GSH, CAT, GSH-Px and CuZn-SOD levels, but did not change the formation of TBARS significantly. In addition, sperm motility, sperm concentration and serum testosterone levels significantly increased, whereas abnormal sperm rate significantly decreased with chrysin treatment. In conclusion, it is suggested that treatment with chrysin can positively affect the reproductive system in rats, and it can be used for the treatment of male infertility.
Keywords: Chrysin; reproductive system; sperm quality; testosterone